Perancangan Sistem Informasi Pendataan Pelanggan Wifi Berbasis Website Pada PT. Infomedia Solusi Net Medan (Jurnal Ilmiah Sains dan Teknologi, 2024)
Initially focused as an internet service provider, PT Infomedia Solusi Net expanded its range of services with software development and digital marketing, reflecting adaptability to technological developments and customer needs. Operating in information and communications technology, the company provides WiFiHome solutions with guaranteed fast internet connections, high security, bandwidth management, and access from various devices. Actively involved in the sales and installation of WifiHome, the company is exploring application development to automate the customer data collection process, intending to improve service quality and operational efficiency. This paper was introduced to overcome the risk of human error in managing customer data. Research methods involve observation, interviews, and literature study. Implementing this system is expected to improve operational efficiency, data accuracy, and availability of customer-related information, provide better service, overcome information search challenges, and optimize customer data management effectively.